Fortification of salted chicken eggs with iodine - Arguez, Lugin Paul S. (2005.)
The study was conducted using a fixed-effects single-factor completely randomized design to determine the effects of iodone fortification on the physico-chemical properties, microbial load, and consumer acceptability of salted chicken eggs.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Fortification; Salted chicken eggs; Iodine